Towards a model of the internationalization system in Colombian higher education: a systems dynamics approach (2020)
Internationalization in higher education institutions is a critical success factor for its consolidation in the global environment. The following article presents a proposal for the construction of a simulation model for the system of internationalization of higher education in Colombia based on systems dynamics. The main characteristics that represent the system were then started and, by means of a causal hypothesis, the variables were gathered in four dimensions. The dimensions that were taken into account were: the global education system, the global higher education institutions, the global territories, and the global citizens. The design of the hypothesis, through system dynamics, allows representing the interactions in each of the dimensions, which finally facilitated the vision of the system as a whole. One of the main results was the dynamic hypotheses which, in turn, allow the construction of the flow and a level diagram for the realization of a computational simulation model. Under this simulation scheme, a novel tool is then proposed for decision-makers regarding the evaluation of the impact of internationalization on the different substantive functions of higher education institutions and the formulation of public policies in this type of system.